E-learning : ASP frameworks - Loh, Chen Hong. (2008)
This research aimed to collect all information about implementation e-learning in current technology. This research is based on the integration of Learning Management System (LMS) model and the Application Service Provider (ASP) business model, to present a design of ASP-oriented LMS.